Gerakan Sosial Baru: Simbol #R4bia - Munadhil Abdul Muqsith (UIN Syarif Hidayatullah Jakarta, 2022)
This paper is to explain how the fusion of social movements and new media produces new social movements. The author himself raised how the #R4bia movement in Egypt and around the world as a form of protest and solidarity with the leader of the Egyptian state President Morsi (2012-2013) was overthrown by Abdul Fattah as-Sisi in a military coup in June 2013. The #R4bia symbol became a trending topic on various social platforms. media. technology is not historically a value-free entity. When a technology product interacts with the user community, the technology product undergoes an adjustment process, in which society gives meaning based on various values. There is a reciprocal relationship and a dialectical dynamic in the process of social construction that is built.